Efficient Fe–Nx/C electrocatalyst for the oxygen reduction reaction derived from porphyrin-encapsulated zeolitic imidazolate frameworks. (18th March 2021) - Park, Jungwon; Kim, Byung Hoon; Kim, Miyeon; Mun, Junyoung; Lee, Chang Yeon
Abstract : Carbon-supported porphyrin-encapsulated and -functionalized zeolitic imidazole frameworks (ZIFs) were pyrolyzed to afford an efficient electrocatalyst for the oxygen reduction reaction (ORR). Abstract : The development of non-platinum catalysts for the oxygen reduction reaction (ORR) in fuel cells is an urgent challenge given the limited reserves of platinum. The Fe–N x /C electrocatalyst possessing isolated atomic metal active sites on N-doped carbon matrices is one of the most promising candidates for platinum-based catalyst alternatives because of its high efficiency and durability. Here carbon-supported porphyrin-encapsulated and -functionalized metal–organic frameworks (MOFs) have been synthesized to afford an Fe-implanted nitrogen-doped porous carbon electrocatalyst via pyrolysis. The fabricated electrocatalyst exhibited outstanding oxygen reduction catalytic activity with a half-wave potential of 0.916 V ( vs. RHE), surpassing state-of-the-art Pt/C (0.891 V). Durability tests revealed that the half-wave potential decreased by only 15 mV after 30 000 cycles. Abundant and well-separated atomic Fe–N x /C active sites in the catalyst play an essential role in the superior ORR activity.